1998
DOI: 10.1016/s1078-5884(98)80158-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative duplex scanning for carotid endarterectomy

Abstract: Intraoperative carotid duplex scanning can be used to assess the immediate technical adequacy of carotid endarterectomy. B-mode image and Doppler flow abnormalities which are reversible can be distinguished from those which require immediate revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
0
22
2
Order By: Relevance
“…1-10 Proponents argue that completion imaging allows surgeons to identify causes of and avert early complications, as well as to ensure good long-term outcomes by avoiding restenosis. 1-8,11,12 Completion imaging with arteriography 3,4,9,10 and duplex ultra-sound 1-13 have been studied extensively and have excellent sensitivity (97% to 100%) and specificity (100%) 5,14 for the intraoperative detection of technical errors during CEA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1-10 Proponents argue that completion imaging allows surgeons to identify causes of and avert early complications, as well as to ensure good long-term outcomes by avoiding restenosis. 1-8,11,12 Completion imaging with arteriography 3,4,9,10 and duplex ultra-sound 1-13 have been studied extensively and have excellent sensitivity (97% to 100%) and specificity (100%) 5,14 for the intraoperative detection of technical errors during CEA.…”
mentioning
confidence: 99%
“…9,15 It is unclear if completion imaging is routinely necessary, which abnormalities require re-exploration, and what effect completion imaging has on outcomes such as 30-day stroke/death or restenosis. 4,7-9,15 Studies attempting to answer these questions have largely consisted of small, single-center series, 1-8,11,12 or were not adequately powered to detect differences in outcomes. 2-7,11,12 …”
mentioning
confidence: 99%
“…1,2 Many of them have also reexamined their own results by means of retrospective studies. 10,11 Nault et al 12 showed that the rate of CEAs in Quebec was similar to that in Ontario during the 1990s, 12 but no province-wide audit of outcomes and appropriateness has been performed. Because the benefit of CEA also depends on how the results of these clinical trials (defining the efficacy) are applied to actual clinical practice (the effectiveness of the procedure), the effectiveness of CEA in Quebec has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have suggested that intraoperative duplex scanning with B-mode imaging (CDU) and hemodynamic assessment of the CEA could be less invasive than completion angiography and as useful to lower the risk of stroke in this group of patients. 10,13,14 The problem with CDU in our practice was the availability of the technologist even if CDU seems to be more cost-effective than completion angiography. 21 Using CDU with small 10 or 15 MHz hockey stick probes, Asher et al 14 found in a series of 650 consecutive cases 2.3% of CEA (n ¼ 15) requiring a surgical revision.…”
Section: Completion Duplex Ultrasonographymentioning
confidence: 99%